The emerging nanotechnology spin-offs: nanophotonics - A. I. Terekhov (Ekonomika Nauki)
The emerging spin-offs have become a way to further spread of nanotechnology in the 2000s. One of them (nanophotonics), which promises a wide range of technological outputs, is considered in this article. Relaying on bibliometric analysis, the most active world players in the field as well as the main domestic institutions participating in the research were identified, their contribution was estimated, and positioning was shown. Considerable attention is paid to the analysis of the research funding structure, the possible linking of scientific input and output. In particular, there were shown: the internationalization of such funding as an element of the globalization of research, a comparative degree of prioritization of nanophotonics on the agenda of a number of science foundations, an example of identifying the most influential grants by combining bibliometric data with information from the Russian Foundation for Basic Research. The source of information was the polythematic database Science Citation Index Expanded, as well as data obtained through the web portals of the Russian Foundation for Basic Research and the US National Science Foundation.